Experimental Investigation of B₄C Particulate Reinforced Aluminium 6061 Based Composite Material in Wire-Cut EDM - Karabulut, Ş.; Gökmen, U.; Karakoç, H.; Kalkan, Ö.K.; Çitak, R. (Металлофизика и новейшие технологии, 2015)
In the present paper, the influences of cutting parameters on surface roughness in wire electric-discharge machining of (WEDM) process of particle-reinforced aluminium AA6061 alloy composite are investigated. The composites are produced using 15% wt. B₄C fraction using powder metallurgy. Experimental trials are performed based on Taguchi L18 (2¹×3²) with a mixed orthogonal array, and the WEDM cutting parameters are optimized for the best surface quality. The investigation results are evaluated by response surface plots and main effect graphs. The machined surface of the metal matrix composite is investigated using scanning electron microscopy (SEM) micrographs. The effect of WEDM machining variables are determined using analysis of variance (ANOVA). The analysis result shows that the most significant cutting parameter is peak current for surface roughness. The SEM and optical micrographs indicate that the reinforced B₄C particles are homogeneously distributed in the matrix structure. Mathematical models are also generated using regression analysis for the surface roughness. Confirmation tests are carried out to determine the prediction performance of the mathematical models, and the surface roughness is predicted with an acceptable mean squared error. В цій роботі досліджено вплив параметрів різання на шерсткість поверхні при обробленні на електроерозійному вирізному станку (ЕЕВС) композита алюмінійового стопу AA6061, армованого частинками. Композити вироблялися з використанням 15% вагової фракції B₄C методою порошкової металургії. Експерименти виконувалися на базі Taguchi L18 (2¹×3²) зі змішаним ортогональним масивом; параметри ЕЕВС-оброблення різанням оптимізувалися, щоб одержати найкращу якість поверхні. Результати досліджень оцінювалися за графіками поверхні відгуку та головного ефекту. Оброблена поверхня композитної металевої матриці досліджувалася з використанням мікрознімків сканівної електронної мікроскопії (СЕМ). Вплив ЕЕВС-оброблення визначався за допомогою дисперсійної аналізи (ДА). Аналіза результатів показала, що найбільш істотним параметром різання для шерсткости поверхні є піковий струм. СЕМ та оптичні мікрознімки показали, що армувальні частинки B₄C розподілені в структурі матриці рівномірно. З використанням реґресійної аналізи були також зґенеровані математичні моделі для поверхневої шерсткости. Випробування на відповідність технічним умовам були виконані з метою попередньої оцінки математичних моделів, і поверхневу шерсткість було спрогнозовано з припустимою середньоквадратичною похибкою. В данной работе исследовано влияние параметров резания на шероховатость поверхности при обработке на электроэрозионном вырезном станке (ЭЭВС) композита алюминиевого сплава AA6061, армированного частицами. Композиты производились с использованием 15% весовой фракции B₄C методом порошковой металлургии. Эксперименты производились на базе Taguchi L18 (2¹×3²) со смешанным ортогональным массивом; параметры ЭЭВС-обработки резанием оптимизировались с целью получения наилучшего качества поверхности. Результаты исследований оценивались по графикам поверхности отклика и главного эффекта. Обработанная поверхность композитной металлической матрицы исследовалась с использованием микроснимков сканирующей электронной микроскопии (СЭМ). Влияние ЭЭВС-обработки определялось при помощи дисперсионного анализа (ДА). Анализ результатов показал, что наиболее существенным параметром резания для шероховатости поверхности является пиковый ток. СЭМ и оптические микроснимки показали, что армирующие частицы B₄C распределены в структуре матрицы равномерно. С использованием регрессионного анализа были также сгенерированы математические модели для поверхностной шероховатости. Испытания на соответствие техническим условиям были проведены с целью предварительной оценки математических моделей, и поверхностная шероховатость была спрогнозирована с приемлемой среднеквадратичной погрешностью.